Perspectives on Nuclear Medicine for Molecular Diagnosis and Integrated Therapy 2016
DOI: 10.1007/978-4-431-55894-1_18
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Imaging with 18F-FMISO PET for Brain Tumors

Abstract: Tumor hypoxia is an important object for imaging because hypoxia is associated with tumor aggressiveness and resistance to radiation therapy. Here, 18 Ffluoromisonidazole (FMISO) has been used for many years as the most commonly employed hypoxia imaging tracer. Unlike F-18 fluorodeoxyglucose (FDG), FMISO does not accumulate in normal brain tissue making it able to provide images of hypoxic brain tumors with high contrast. Clinical evidence has suggested that FMISO PET can predict patient prognosis and treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…72 [ 18 F]fluoromisonidazole is reduced and retained by viable hypoxic cancer cells and is used for defining hypoxic volumes and for noninvasive grading of glioma. 83 An attractive application is escalating radiotherapy doses to [ 18 F]fluoromisonidazole-positive tumor regions, which are hypoxic and therefore likely to be radioresistant. 84 Studies are under way to determine whether there is any clinical benefit from this approach.…”
Section: Other Metabolic Tracersmentioning
confidence: 99%
“…72 [ 18 F]fluoromisonidazole is reduced and retained by viable hypoxic cancer cells and is used for defining hypoxic volumes and for noninvasive grading of glioma. 83 An attractive application is escalating radiotherapy doses to [ 18 F]fluoromisonidazole-positive tumor regions, which are hypoxic and therefore likely to be radioresistant. 84 Studies are under way to determine whether there is any clinical benefit from this approach.…”
Section: Other Metabolic Tracersmentioning
confidence: 99%
“…Note the very high spatial (0.5×0.5 mm 2 pixel −1 ) and temporal (356 ms) resolution that can be potentially achievable with HP 15 N MRI of [ 15 N 3 ]nimorazole—first two images in each series are shown for two different projection views. This proof‐of‐principle demonstration opens the prospects for utilization of SABRE 15 N hyperpolarization of [ 15 N 3 ]nimorazole in bioimaging applications such as reporting on tumor hypoxia status in a manner similar to that of nitroimidazole‐based PET tracers [43–45] …”
Section: Resultsmentioning
confidence: 95%
“…SABRE‐SHEATH was shown to hyperpolarize metronidazole, [40] the FDA‐approved antibiotic that can be safely administered in large doses of up to several grams [41, 42] . This antibiotic is structurally similar to many nitroimidazole‐based 18 F‐labeled radiotracers, employed for hypoxia imaging in cancer and other diseases [43–45] . More recently, we have demonstrated that spin‐relays [46, 47] can provide efficient polarization of 15 N‐ 15 N spin‐spin coupled sites in metronidazole with − 15 NO 2 group gaining high levels of polarization (>16 %) and very long T 1 of ≈10 min [48] .…”
Section: Introductionmentioning
confidence: 99%